EFFICIENCY OF UTILIZATION OF FACILITY COLD STORAGE PT. GOLDEN CUP SEAFOOD IN OCEAN FISHING PORT OF BELAWAN NORTH SUMATRA - Muhammad Fauzi Faruza; Jonny Zain; Ronald M H (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on March 2015 in ocean fishing port of Belawan, Medan,province of North Sumatra. The objective is to of the investigate level efficiency forutilization of cold storage facilities. The method using is survey method. Existing facilities atthe PT. Golden Cup Seafood is cold room I, cold room II, semi contact/multiplate freezer andair blast freezer (ABF). Cold room I utilization rate is 75% and the utilization efficiency rateof 90%. The utilization for cold room II is 101.4% and level of efficiency for its utilization is75%, for semi contact/multiplate freezer both level of utilization and efficiency are 100%.The utilization rate of air blast freezer (ABF) is 39.1% and the rate of utilization efficiency of42.8%, for tool namely hand lift, the utilization rate of 66.6% and the level of efficiency ofutilization is 100%. from the analysis of the efficiency of utilization of cold storage facilities,that almost all the facilities already be used properly and efficiently only require an increasein good layout arrangement and preparation design to increase the utilization and efficiencyof existing facilities.Keywords: Efficiency, utilization, cold storage